The Games Infants Play: Social Games During Early Mother–Infant Interactions and Their Relationship With Oxytocin - Markova, Gabriela (Frontiers in Psychology, 2018)
The present study examined early social game routines during natural face-to-face mother–infant interactions and their relationship with oxytocin. Forty-three mother–infant dyads were observed, when infants were 4 months old, during a procedure involving a baseline and a natural interaction, where mothers were instructed to interact with their infants as they would at home. During this procedure four saliva samples from mothers and infants were collected to determine levels of oxytocin at different time points. Social game routines and infant social engagement (gaze, positive, and negative affect) were coded during the natural interaction. Social games were observed in 76.7% of the mother–infant dyads, and 46 different types of games were identified. Mothers initiated games to re-engage infants significantly more often than when infants were already engaged with them. During the games, infants showed more positive affect and less negative affect in comparison to the rest of the interaction. Finally, maternal increase in oxytocin from before to after the natural interaction was positively correlated with game rate and time spent in games, while infant increase in oxytocin from before to after the natural interaction was inversely related to game rate. These results indicate that social games are an inherent part of early mother–infant interactions, and their occurrence is associated with oxytocin of both infants and mothers.